Interobserver and interequipment variability of hepatic, splenic, and renal arterial Doppler resistance indices in normal subjects and patients with cirrhosis - Sacerdoti, David; Gaiani, Stefano; Buonamico, Paolo; Merkel, Carlo; Zoli, Marco; Bolondi, Luigi; Sabbà, Carlo (Journal of hepatology, 1997)
Background/Aims: Doppler arterial resistance indices are used to evaluate alterations in arterial hemodynamics in the liver, spleen, and kidney. The purpose of this study was to determine the interobserver and interequipment variability of hepatic, splenic, and renal arterial Doppler resistance indices, and the influence of a cooperative training program of the operators on the reproducibility of the results. Methods: In the first part of the study, hepatic (PI-L, RI-L), splenic (PI-S, RI-S), and renal (PI-K, RI-K) pulsatility and resistive indices were measured by echo-color-Doppler in eight control subjects and ten patients with cirrhosis by three operators using three different machines. In the second part of the study, measurements were taken by the three operators in nine controls and nine patients with cirrhosis, after cooperative training, with a single machine. Results: Significant interobserver variability was present for all parameters except RI-L. Significant inter-equipment variability was present for all parameters except PI-S and RI-S. Only 0–3% of variance was equipment- or operator-related, while 58–72% was patient-related. Hepatic and renal coefficients of variation were similar in patients with cirrhosis and controls, while splenic coefficients of variation were higher in patients with cirrhosis than in controls. After training, differences among operators disappeared for all variables except RI-K, and the operator-related component of variance nearly disappeared for all parameters. Conclusions: Hepatic, splenic, and renal arterial resistance indices show small but significant interobserver and interequipment variability. Interobserver variability can be decreased to non-significant levels by a common training program. Thus, these indices can be widely applied to the study of arterial circulation in these organs.